CRIMES OF MANUFACTURING AND SELLING PHARMACEUTICALS IN A WAY TO DANGER THE LIVES AND HEALTH OF INDIVIDUALS (Evaluation of Türkiye and Uzbekistan legal system) - Mirakhmedova, Fazilat (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
This study focuses on the crimes of producing and selling drugs that endanger people's lives and health. These types of crimes are common, especially in low- and middle-income countries, and can pose serious threats to public health in these countries. Based on different opinions and information, the causes and consequences of these crimes have been examined.